12. EFFECTIVENESS OF APPLICATION ONLINE TREATMENT INFORMATION SUMMARY FORM AT HCMC EYE HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Ho Chi Minh Eye Hospital has digitized the Online Treatment Information Summary Form to create conditions for patients to update their knowledge about the disease and participate with doctors in the treatment process.Purposes: Evaluate the effectiveness of using online treatment information summary sheets at the Eye Hospital in 2023Methods: A descriptive cross-sectional study analyzed 662 patients with eye disease treatments who were discharged from the hospital and returned for follow-up examinations at the Eye Hospital to evaluate the effectiveness of applying the Online Treatment Information Summary Form for patients instituted in 2023.Results: There were 87.5% of people know how to use the Summary Form, 72.2% of them having knowledge, 73.3% having a positive attitude, and 70.8% practicing good health care after consulting the Summary Form. We found a statistically significant relationship between a number of factors and knowledge, attitudes, and health care practices after eye patients consulted the Online Treatment Information Summary Form: group, age, education level, occupation, living area, economic status, treatment indications, and frequency of hospitalization for treatment during the year.Conclusion: It is necessary to maintain communication work to raise awareness among patients about the importance of the Online Treatment Information Summary Form.
Keywords: Online Treatment Information Summary Form